Топологический анализ триангуляционных 3D моделей изделий - Доброскок, Владимир Ленинмирович; Фадеев, Валерий Андреевич; Абдурайимов, Л. Н.; Чернышов, С. И. (НТУ "ХПИ", 2011)
Рассмотрены подходы к топологическому анализу триангуляционных 3D моделей изделий. Анализ основан на определении дифференциальных (поэлементный анализ смежности граней, ребер и вершин) и интегральных (эйлерова характеристика и род поверхности) характеристик. Предложен обобщенный подход, позволяющий выполнять топологическую верификацию твердотельных триангуляционных моделей.

The approaches to the topological analysis of triangulation of 3D models of products. The analysis is based on determining the differential (partial analysis of adjacency of faces, edges and vertices) and integral (Euler characteristic and genus of the surface) characteristics. A generalized approach that enables the verification of a topological triangulation of solid models.
The topological analysis triangulable 3D models of products
Keywords: дифференциальные характеристики; интегральные характеристики; топологическая верификация; solid models; integral characteristics; differential characteristics